2006
DOI: 10.1164/rccm.200509-1525oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Inflammation and Bronchial Bacterial Colonization in Chronic Obstructive Pulmonary Disease

Abstract: Bacterial colonization is associated with neutrophilic airway lumen inflammation in ex-smokers with COPD and could contribute to progression of airway disease in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
217
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(244 citation statements)
references
References 36 publications
14
217
1
12
Order By: Relevance
“…NTHI infection has been associated with the initiation of inflammatory exacerbations of COPD (34)(35)(36)(37). Our work shows that in an elastase-treated mouse lung, which mirrors the pathology of a COPD lung, parental strain NTHI survives better than in an untreated lung infection.…”
Section: Discussionmentioning
confidence: 69%
“…NTHI infection has been associated with the initiation of inflammatory exacerbations of COPD (34)(35)(36)(37). Our work shows that in an elastase-treated mouse lung, which mirrors the pathology of a COPD lung, parental strain NTHI survives better than in an untreated lung infection.…”
Section: Discussionmentioning
confidence: 69%
“…One example is the association between hepatitis B and C virus and the incidence of hepatocellular carcinoma [74]. In smokers, the establishment of chronic microbial colonisation in the lungs is seen, even in the absence of airway obstruction, and this persists in ex-smokers with COPD [75]. Unlike the sterile lungs of a healthy individual, we know that there is a failure of the innate immune system in COPD.…”
Section: The Role Of Inflammationmentioning
confidence: 99%
“…Lungs of COPD patients are often colonized or infected with Haemophilus influenzae, Moraxella catarrhalis, Streptococcus pneumonia, and Pseudomonas aeruginosa (Murphy et al, 2004;Sethi et al, 2006). Culture-independent approaches showed that the microbiome of the COPD lung differs significantly from the microbiome of healthy lungs (Erb-Downward et al, 2011;Sze et al, 2012;Zakharkina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%